THE “FROZEN CONFLICT” THAT TURNED HOT: CONFLICTING STATE-BUILDING ATTEMPTS IN SOUTH OSSETIA - LEMAY-HÉBERT, Nicolas (CENTRAL ASIA AND THE CAUCASUS, 2008)
The South Ossetians living under the authority of the unrecognized Republic of South Ossetia make up one of those peoples, like their fellow Caucasians the Abkhazes or the Transnistrians, trapped in a complete juridic political limbo. The political entities that “claim the monopoly of the legitimate use of physical force”1 over them is not those juridically representing them in the international arena. Having met three of the four criteria required to be recognized as a state according to the Montevideo Convention on the Rights and Duties of the State (1933)—that is to say, having a permanent population, a defined territory and a government—the de facto authorities still crave international recognition.2 This situation is more than a mere juridical imbroglio. It has concrete and specific repercussions for the people living in these territories. Stuck in the midst of competing state-building attempts, from the de facto authorities wanting to cling to power to the de jure authorities trying to extend their influence over the territory, the local population finds itself politicized from all sides. Generally dubbed “frozen conflicts,” especially in the Caucasus (in South Ossetia, Abkhazia and Nagorno-Karabakh) and in Transnistria, this actual denomination ignores the dynamic logic at work in these regions.3 The recent conflict in South Ossetia, triggered by the Georgian assault on Tskhinvali on 7 August and the following military response by the Russian army, clearly showed the limits of this perspective. After describing the current political setting in South Ossetia and examining the logic of a “zone of conflict,” this article analyzes the oppositional logic between the competing state-building attempts in South Ossetia, led by Russia and Georgia, respectively. Showing how the local population is literally squeezed between the militarization of both parties, the article contends that South Ossetians themselves ought to be taken into account in order for a genuine state- building process to take root in South Ossetia